Biosorption of reactive yellow dye by malt bagasse - Bruna C da Silva; Adriane Zanutto; Juliana MTA Pietrobelli (Adsorption Science & Technology)
This research evaluated the biosorption potential of the 134% Yellow Reafix BR2 dye by the malt bagasse. Tests were conducted at batch conditions, under controlled agitation, pH, and temperature. The biosorbent was characterized through scanning electron microscopy and Fourier transform infrared spectroscopy, before and after biosorption. Malt bagasse presented a point of zero charge at 6.75. In the process variables evaluation, there was a greater biosorption potential in acidic pH, without a significant influence of size on the biosorbent particles. The equilibrium time was achieved in 360 min, with approximately 93% removal at the evaluated temperatures. The experimental data were best represented by the pseudo-second-order model. Biosorption was characterized as spontaneous and endothermic, with indicative of physical. Considering the equilibrium, the Langmuir isotherm was the one that best fit the experimental data, with a maximum biosorption capacity of 68.75 mg g –1 (at 303 K and pH 2). The removal suffered no significant interference with the presence of another dye nor with the increase of ionic strength. Thus, the malt bagasse shows potential to be used as a biosorbent in treatment systems of industrial effluents.